Comparative Performance Of Loose Sandy Soils Improved By Deep Compaction Techniques - Majid, Moho Farid Ahmad @ (2005)
The objectives of the study were to determine the effect of fine content on the improvement of cohesionless loose sandy soils, to evaluate and compare the effectiveness of the dynamic compaction and vibro-compaction techniques, to provide suitable semi empirical models on improvement and finally to propose a suitable comparative performance chart that can help select the technique that provided higher improvement. The research was conducted at study sites in Kerteh, Terenggam.i. Based on improvements made, it was found that the increase in soil resistances after completion of treatment differs between the two techniques. Extensive soil samples were then collected using specially fabricated sampling tube, and wet sieve grading analyses on the soils were performed in the laboratory to determine the difference in fine content. Models were then developed to determine the relations between improvement against soil resistance. Cubic semi-empirical models were found to be the best models for both dynamic compaction and vibro-compaction. The models allowed direct usage of the cone resistance to evaluate the performance of the deep compaction technique incorporating the effect of fine content. The models were then used to produce a suitable comparison chart that can assist engineers in designing the compaction techniques.